Leveling the Playing Field: Perspectives of People with Disabilities on Reasonable Accommodations Received to Engage in Public Recreation - Devine, Mary Ann (Disability Studies Quarterly, 2015)
According to the ADA, people with disabilities have the right to participate in public park and recreation services. Important gains in their access to activities of their choosing since the ADA was written into law, in part due to individuals being able to request reasonable accommodations. The purpose of this study was to understand the perspectives of people with disabilities who participate in public park and recreation services on whether their accommodation needs are met and if they are effective in facilitating meaningful recreation experiences. Participants reported requesting reasonable accommodations was a way to exercise civil rights and gain access to meaningful recreation activities. They also reported a duality in requesting accommodations in that they were met with confusion, lack of understanding, and reluctance. It is recommended that the park and recreation profession undergo a paradigm shift and embrace making reasonable accommodations as an important professional skill.